AL-QUR’AN DAN SASTRA: ANTARA ETIKA, ESTETIKA, DAN PROFETIKA - Abd. Aziz (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2020)
This paper aims to explore the meaning of a verse in the Al-Qur'an which is actually a message, bringing memories to reality, namely that although it is integrated into the Arabic linguistic system, the text of the Al-Qur'an has its own characteristics. The Qur'an, a unique text, makes use of a certain lively and dynamic 'linguistic code' to transfer its distinctive 'treatise'. This peculiarity was later recognized by the Arabs, and even made the people who attacked the treatise admire. Starting from the various uniqueness possessed by the Al-Qur'an, and moreover, there arose a challenge from the Qur'an itself to the Arabs to replicate, duplicate, and create something new on a number of texts such as the Qur'an, for example the letter -a letter in short, gave birth to the idea of ​​the absolute 'incommensurability (i'jaz)' of the Qur'an. A study of solving social complexity that can create harmony amidst the variability of society.